2004
DOI: 10.1038/sj.ijo.0802788
|View full text |Cite
|
Sign up to set email alerts
|

Influence of social class on time trends in BMI distribution in 5-year-old French children from 1989 to 1999

Abstract: AIMS:To assess the prevalence of obesity and changes in body mass index (BMI) distribution between 1989 and 1999 in 5-y-old children, and to study the influence of parental socioeconomic status on these parameters. METHODS: Two cohorts of children in the final year of nursery school (in the city of Lille, France) were enrolled in 1989 (705 children: mean age ¼ 5.670.4 y) and 1999 (1258 children: mean age ¼ 5.670.5 y). Weight and height were measured, and data about parental occupation were collected during a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
34
1
6

Year Published

2007
2007
2012
2012

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 35 publications
8
34
1
6
Order By: Relevance
“…Until very recently, almost all published studies examining trends in overweight and obesity over time in preschool children have demonstrated increasing prevalence, 1,10,11,14,15,[28][29][30][31][32] with the only exceptions usually occurring in low income countries. 1 A study of 4-year-old children in a single region in Sweden, comparing routinely collected anthropometric data from 2002/03 to 2007/08, however, found an apparent secular trend to decreasing prevalence of overweight and obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Until very recently, almost all published studies examining trends in overweight and obesity over time in preschool children have demonstrated increasing prevalence, 1,10,11,14,15,[28][29][30][31][32] with the only exceptions usually occurring in low income countries. 1 A study of 4-year-old children in a single region in Sweden, comparing routinely collected anthropometric data from 2002/03 to 2007/08, however, found an apparent secular trend to decreasing prevalence of overweight and obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Childhood obesity has been unambiguously linked to lower educational levels and low parental social class, 53,54 and the influence of social factors can seem very early in life. 55 Unhealthy habitsFsuch as high-fat diets, low levels of physical activity and exposure to chronic stressFare seen more frequently in families with a low SES. [5][6][7][8] This was also reported by MacFarlane et al 56 explaining that adolescents with a low SES were more likely to report that they were allowed to watch television during meal times and that unhealthy foods were usually available at home.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, using entitlement to free school meals as a proxy for income 160 , Cecil et al 160 found that it was not that these deprived children weighed more than their more affluent peers, but that in fact the higher BMI was due to shorter height, suggesting possible nutrition-related growth restriction in low-income families. Also, children from families with lower education levels have a higher risk of obesity 128,161,162 . However, this effect could be mediated by confounding factors, such as low income and lower levels of cognitive stimulation 121 .…”
Section: The Neighbourhood Environmentmentioning
confidence: 99%